Caracterização e estudo de envelhecimento de isolador tipo pino em PEAD utilizado no setor elétrico - Cynthia D' Avila Carvalho Erbetta (2015)
The study of polymeric material behavior used in the composition of insulators of the electrical system has a fundamental importance in evaluating their lifetime, as well as their performance in different environmental conditions. The effect of polymeric insulators pin-shaped (15kV) of high density polyethylene (HDPE) under accelerated aging. Three aging chambers were used, two chambers of artificial weathering were used (radiation, temperature and humidity) and one of electric stress (voltage and humidity), where the last was projected and constructed in this work. The ASTM G155 was used as reference for one of the weathering chambers, and other parameters to natural aging conditions were established considering the metropolitan area of Belo Horizonte (summer and winter cycles). In order to evaluate the effect of accelerated aging on the sample-shaped were used in the tests sample bowtie-shaped, plates and insulator (as is used in service). The samples were aged at 200, 1,000 and 2,000h. The scope of work included the design, installation and operation of electrical stress chamber. The samples before and after accelerated aging, were characterized by the following techniques: visual inspection, hydrophobicity, leakage current measurement, rheometry, Fourier transform infrared spectrometry (FTIR), scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), thermogravimetry (TG), differential scanning calorimetry (DSC), mechanical tests and determination of dielectric strength. The results showed different behavior of the aged samples, due to the aging method applied and the sample shape. The electric stress applied to the chamber constructed was effective. There is strong evidence that during accelerated aging for all the methods applied, there was migration of additives to the surface of the samples. The loss of hydrophobicity in insulators with 1.000h of aging was more expressive and with 2.000h was total. Despite the leakage current measurement not shown significant results until 1.000h of accelerated aging, it is possible that it can contribute significantly in the evaluation from 2.000h, due to the loss of hydrophobicity. By rheometry was obtained evidence of degradation intensity, too indicated by FTIR. This technique showed that rheological behavior of samples subjected to aging with 1.000hs was altered. Analysis by SEM / EDS to evaluate the effect of aging on the topography of the sample, and to identify the chemical elements present on the sample surface. TG was used to estimate the lifetime of the samples, considering only the effect of temperature and nitrogen atmosphere. The OOT analysis (oxidation onset temperature) by DSC indicated a difference between the oxidative stability of the samples. The crystallinity, within the estimated time interval, showed insignificant in the evaluation of accelerated aging. The mechanical and electrical tests were not appropriated to evaluate samples with degradation still in superficial level. Among the techniques applied, those identified with potential for application in the study of the correlation between aging natural and accelerated are: measure hydrophobicity, OOT, carbonyl index and measure of average molar mass. This work has as unprecedented result: project, construction and operation of an electric stress chamber for insulating type pin or pillar, implementation and characterization of samples under accelerated aging in different shapes, including the insulator as applied in service. In addition, by first time, weathering cycles were established (summer and winter) in order to get a good correlation between the conditions of the natural and the artificial environment, based on meteorological data in the metropolitan region of Belo Horizonte.